Towards the development of bench testing for lower-limb prosthetic sockets for sport applications - Gariboldi, F.; Scapinello, M.; Sanchez Salazar, P. A.; Migliore, G. L.; Teti, G.; Cutti, A. G.; Petrone, N. (ISBS Proceedings Archive (Michigan), 2022)
Prosthetic sockets are the bespoken part of lower-limb prostheses. Knowledge about the mechanical properties of sockets is essential to ensure patient safety and comply with current medical device regulations. This includes sockets designed for sport activities. Unfortunately, the literature is extremely limited and contradictory as described in a recent systematic review. The aim of this study was to initiate a research activity aiming to design a mechanical bench system for socket testing and perform a comparative analysis of the ultimate strength of alternative socket layups. Results highlight substantial differences in the maximum loading at failure, stressing the importance of increasing the knowledge about socket mechanical properties to support prosthetists provide reliable and safe products to patients and athletes.